The just meaningful difference in speech-to-noise ratio - McShefferty, David; Whitmer, William M.; Akeroyd, Michael A. (Sage, 2016)
The speech-to-noise ratio (SNR) in an environment plays a vital role in speech communication for both normal-hearing (NH) and hearing-impaired (HI) listeners. While hearing-assistance devices attempt to deliver as favorable an SNR as possible, there may be discrepancies between noticeable and meaningful improvements in SNR. Furthermore, it is not clear how much of an SNR improvement is necessary to induce intervention-seeking behavior. Here we report on a series of experiments examining the just-meaningful difference (JMD) in SNR. All experiments used sentences in same-spectrum noise, with two intervals on each trial mimicking examples of pre- and post-benefit situations. Different groups of NH and HI adults were asked (a) to rate how much better or worse the change in SNR was in a number of paired examples, (b) if they would swap the worse for the better SNR (e.g., their current device for another) or (c) if they would be willing to go to the clinic for the given increase in SNR. The mean SNR JMD based on better/worse ratings (one arbitrary unit) was similar to the just-noticeable difference, approximately 3 dB. However, the mean SNR JMD for the more clinically relevant tasks -- willingness (at least 50% of the time) to swap devices or attend the clinic for a change in SNR -- was 6-8 dB regardless of hearing ability. This SNR JMD of the order of 6 dB provides a new benchmark, indicating the SNR improvement necessary to immediately motivate participants to seek intervention.